Relationship between work-family conflict and work, family and community domains demands and resources: A longitudinal study - Hassan, Zaiton; Sabil, Surena; Bandar, Nur Fatihah Abdullah; Ibrahim, Dayang Kartini; Nor, Nik Norsyamimi Md (International Journal of Engineering and Technology, 2018)
Shifting from Western-dominated perspectives, demands and resources from the community domain were investigated, together with work and family domains to predict work-family  conflict and family-work conflict. Pearson correlation analysis was conducted on data obtained through two self-report questionnaires completed three months apart by 277 executives and non-executives from three public and private sector organizations in Sarawak, East Malaysia. After controlling for conflict at Time 1, work demands were positively related; while work resources were negatively related to work-family conflict and family work conflict at Time 2. In addition, community demands were related positively to  work-family conflict and family work conflict at Time 2.  This study underscores the roles of community which has been neglected in Western studies, as important in affecting  work-family conflict and family-work conflict  in Malaysia.  Therefore, to improve our understanding on work-family conflict in a society which is predominantly collectivist, aspects of community should be included.